2006
DOI: 10.1016/s1130-1473(06)70315-3
|View full text |Cite
|
Sign up to set email alerts
|

Valor predictivo de la clasificación de Knosp en el grado de resección quirúrgica de los macroadenomas invasivos. Estudio prospectivo de una serie de 23 casos

Abstract: The Knosp classification alone cannot predict the behavior of these tumors. In our experience, despite tumor extension to the cavernous sinus, pituitary macroadenomas can be safely resected with low morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our search identified 1238 references ( Figure 1). Nineteen articles were potentially eligible for inclusion in our review, and from these 12 were excluded because they involved retrospective comparisons (2,3,5,(15)(16)(17)(18)(19)(20)(21)(22)(23) and two were excluded because they were publication of case series (24,25). Five publications were included in the final analysis (4,6,(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 1238 references ( Figure 1). Nineteen articles were potentially eligible for inclusion in our review, and from these 12 were excluded because they involved retrospective comparisons (2,3,5,(15)(16)(17)(18)(19)(20)(21)(22)(23) and two were excluded because they were publication of case series (24,25). Five publications were included in the final analysis (4,6,(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Knosp invasion grades could give more information about the possible extent of resection, which is described by many authors. 12,13,15,16,[19][20][21][22] Knosp grade of invasion of the cavernous sinus is widely described as one of the most important factors to consider before pituitary adenoma surgery, being unfavorable as the grade goes higher. This invasion represents a negative prognostic factor, reducing the probability of success in surgical treatment, in terms of both complete tumor resection and hormonal remission in functioning tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This invasion represents a negative prognostic factor, reducing the probability of success in surgical treatment, in terms of both complete tumor resection and hormonal remission in functioning tumors. 12,13 Dallapiazza et al found that tumors with Knosp grades 0 to 2 and volumes up to 10 cm 3 had more chance to get a gross total resection, with Knosp grade being the only independent predictor in a multivariate analysis. 21 In our study, Knosp grade had a correlation with the extent of resection, but it did not result as an independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…En los macroadenomas la tasa de remisión es menor y ha sido reportada entre el 17 y 68% 9,52 ]; en nuestra serie fue del 68,4% (13/19). La dificultad en la resección quirúrgica completa podría deberse en microadenomas a sangrado de senos intercavernosos, imposibilidad de reconocer la lesión y sus márgenes; y en macroadenomas fundamentalmente al grado de invasividad 53,54 ] . A pesar de la remisión clínica y bioquímica, la recurrencia de la EC han sido reportada en el 2-35% de los pacientes, dependiendo de los criterios de curación y el tiempo de seguimiento 31,55 .…”
Section: Discussionunclassified